Study on the status and countermeasures of disease self-management ability in chronic kidney disease patients in cold regions - Wei Xinrui; Li Chunlian; Yu Hongmei; Xu Lingling; Meng Siwen; Xing Chun; Gao Qiang; Chang Guangming; Wang Yongchen (Frigid Zone Medicine)
Effective Chronic Kidney Disease (CKD) management is particularly important in cold regions of China, where climate and lifestyle factors play significant roles. However, there is a lack of relevant studies in this area. Therefore, the purpose of this study was: (1) to assess the status of self-management capacity in individuals with CKD in cold regions of China and analyze the factors influencing it; (2) to identify strategies to improve CKD management in primary care settings in these regions; and (3) to understand patients' attitudes toward eHealth services.